Describing The Catalytic Role Of Alkaline Earth Metals On The Thermal Activation Of Cellulose - Facas, Gregory (My University, 2020)
Biomass fast pyrolysis has considerable potential for the production of renewable fuels and chemicals. Despite pyrolysis being studied for more than a hundred years, only a few commercial pyrolysis processes exist as the optimal feedstock composition and reaction conditions for this process remain unknown. The lack of process optimization can be attributed to the multiscale complexity of the process. During pyrolysis the constituents of biomass are fragmented in a matter of seconds through thousands of chemical reactions, that occur in multiple phases, and are simultaneously competing with various heat and mass transfer processes. All of these fundamental phenomena are understood poorly within pyrolysis literature. Pyrolysis is further complicated by alkali and alkaline earth metals that are naturally present in lignocellulosic biomass. These metals are known to alter pyrolysis chemistry and catalyze the initial breakdown of the polymer constituents of biomass. The main objective of this thesis was to investigate the mechanistic role of alkaline earth metals on the initial fragmentation of cellulose, the main component of biomass. Fundamental knowledge into pyrolysis chemistry has been limited previously due to an inability to obtain intrinsic kinetic, a critical tool used to validate reaction mechanisms. The requirements for proper measurement of high temperature (>400 °C) biomass pyrolysis kinetics are presented. Most importantly, these requirements mandate that for proper measurement of kinetic data, experimental techniques must heat and cool reaction samples sufficiently fast to elucidate the evolution of reaction products with time, while also eliminating substantial reaction during the heating and cooling phases. The ability of the PHASR (Pulse Heated Analysis of Solid Reactions) micro-reactor technique and other common pyrolysis reactor techniques to satisfy these requirements was discussed. PHASR can thoroughly satisfy all the requirements for measuring pyrolysis kinetics unlike other conventional reactor techniques. The PHASR technique was then utilized to study the kinetics of calcium assisted activation of cellulose. Conversion of calcium doped films of α-cyclodextrin, a known cellulose surrogate, was measured over a range of reaction temperatures (370-430 °C) and calcium concentrations (0.1-0.5 mmol Ca2+/g CD). The rate of conversion of α-cyclodextrin was significantly accelerated by the presence of calcium. Activation was shown to have a second order rate dependence on calcium concentration, suggesting the involvement of two calcium ions in the mechanism. First principle density functional theory calculations were performed on calcium catalyzed glycosidic bond cleavage and depict calcium as having two catalytic roles of disrupting hydrogen bonding in the cellulose matrix and stabilizing the transition state. The energetics from experiment and computations agree closely representing the first atomistic mechanism of metal catalyzed activation utilizing both experiments and computations. Kinetics of magnesium assisted activation were then measured with PHASR experiments to discern any effects from the size of the catalytic ion on activation chemistry. PHASR experiments were performed in identical temperature and metal concentrations to the calcium experiments. Magnesium assisted activation exhibited identical behavior to the calcium case with energetics of activation matching within experimental error.
University of Minnesota Ph.D. dissertation. 2020. Major: Chemical Engineering. Advisor: Paul Dauenhauer. 1 computer file (PDF); 99 pages.
Keywords: Biofuels; Biomass; Catalysis; Kinetics; Pyrolysis